Human Resource Management Skills Required of Colleges of Education Administrators in Kano State of Nigeria - ONYEKABA, MARTHA NNAMAKA (International Journal of Educational Management, 2021)
This study was conducted to determine the human resource management skills required of college of education administrators in Kano state of Nigeria. The study employed a descriptive survey design. Four research questions were developed to guide the study. The population of this study consisted of all administrative staff in the three colleges of education in Kano State whose population at the time of study was 627. Purposive random sampling technique was employed to use two out of the three colleges of education in Kano State out of which a sample size of 220 administrative staff were randomly drawn using simple random sampling technique. The instrument for data collection was a questionnaire titled: Human Resource Management Skills Questionnaire (HRMSQ) which consisted of 20 items and was validated by experts in the field of study. The four areas of human resource management skills were tested for reliability with Cronbach Alpha internal consistency of 0.89, 0.86, 0.91 and 0.88 respectively. Data collected were analyzed using simple descriptive statistics of weighted mean and standard deviation to answer the research questions with a mean score cut-off point of 2.50. The study found out that all the skills of human resource management need to be emphasized in time of management for efficiency. It was therefore recommended among other things, that administrators of colleges of education in Kano state should ensure that the number of lecturers employed are devoid of favoritism and sentiments for improved performance. Conclusions were also drawn.